2014
DOI: 10.1021/ja502174d
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Intermolecular C–H Amination of (Hetero)arenes via Transient Unsymmetrical λ3-Iodanes

Abstract: A one-pot two-step method for intermolecular C-H amination of electron-rich heteroarenes and arenes has been developed. The approach is based on a room-temperature copper-catalyzed regioselective reaction of the in situ formed unsymmetrical (hetero)aryl-λ(3)-iodanes with a wide range of primary and secondary aliphatic amines and anilines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 108 publications
1
49
0
Order By: Relevance
“…44 A regioselective direct C-H amination of the 7-deazapurines to give access to the 8-amino-, 45 or 7-amino-7-deazapurine analogues has been also reported. 46 We found that treatment of tubercidin 1b with benzotriazole (2 equiv.) in the presence of I 2 (0.4 equiv.)…”
mentioning
confidence: 93%
“…44 A regioselective direct C-H amination of the 7-deazapurines to give access to the 8-amino-, 45 or 7-amino-7-deazapurine analogues has been also reported. 46 We found that treatment of tubercidin 1b with benzotriazole (2 equiv.) in the presence of I 2 (0.4 equiv.)…”
mentioning
confidence: 93%
“…Even in the presence of a strong acid, the iodonium addition to the aromatic substrate is successful only with benzenes that are more electron-rich than toluene. Furthermore, the TIPP-I(OH)OTs reagent is more effective than the mesityl (Mes) based congener, 78 because the bulky TIPP is completely nontransferable to the amine from the standpoint of the unsymmetrical diaryl- λ 3 -iodane. Most importantly, the C–N bond formation is highly regioselective, since the intermediate diaryl- λ 3 -iodanes feature para substitution with respect to the most electron-releasing substituent of the aromatic substrate.…”
Section: Pertinent Examples Of Catalytic Amination Of Benzenesmentioning
confidence: 99%
“…[11][12][13][14] One of the most efficient reagents are N-chlorosulfonamides under Pd/Cu catalysis. 13 Inspired by related C-H aminations of indoles, 13 we decided to study the C-H aminations of pyrrolo[2,3-d]pyrimidines (7-deazapurines).…”
Section: Introductionmentioning
confidence: 99%